The Influence of Profitability, Leverage, Liquidity and Company Size on Dividend Policy - Wiasih, Dina Retno; Tubastuvi, Naelati; Purwidianti, Wida; Bagis, Fatmah (SENTRALISASI, 2024)
This research aims to determine the influence of profitability, leverage, liquidity and company size on dividend policy. This research uses quantitative methods, purposive sampling techniques, and multiple regression analysis with SPSS 26. 27 primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period constitute the population in this study and the number of observation samples is 108. The methodological approach uses purposive sampling, namely a non-probability sampling technique, to ensure the intended sample size, namely with the criteria of companies that distribute their financial reports in rupiah, companies that earn profits every year, and companies that distribute dividends. This research shows the results that liquidity has a positive and significant effect on dividend policy, leverage has no significant effect on dividend policy, profitability and company size have no effect on dividend policy.